Analisis Produktivitas dan Faktor-Faktor yang Memengaruhi Efisiensi Asuransi Syariah di Indonesia: Suatu Kajian Empiris - Dede Iskandar; Noer Azam Achsani; Setiadi Djohar (Department of Islamic Economics, IPB University, 2020)
Market share on Islamic Insurance is still very small compared to conventional insurance. Islamic insurance companies must be able to compete with conventional insurance in order to increase their market share. Efficiency and Productivity are factors that must be improved so that Islamic insurance can compete with conventional insurance. This study aims to analyze the level of efficiency and productivity of Islamic insurance during the 2016-2018 period. The study was conducted on 48 Islamic insurance companies consisting of 26 Islamic life insurance companies and 22 Islamic general insurance companies. Efficiency analysis use the Data Envelopment Analysis (DEA) approach and productivity analysis use the Malmquist Productivity Index (MPI). The novelty of this study, among others, involves Islamic general insurance in the productivity analysis which has not been studied so far. The results of the analysis shows that the majority of Islamic life insurance and Islamic general insurance are inefficient during the 2016-2018 period. The size of the company which represents the total assets is the factor that have a positive and significant effect on the efficiency value. The results of the productivity analysis shows that the productivity level of both sharia life insurance and general sharia insurance during the 2016-2018 period is influenced by technological change factors.